Preparation and study of porous MnCo2O4@NiO nanosheets for high-performance supercapacitor. Issue 16 (November 2019) - Cheng, Bingbing; Zhang, Wei; Yang, Mo; Zhang, Yujie; Meng, Fanbin
Abstract: Porous MnCo2 O4 @NiO nanosheets have been produced through hydrothermal synthesis and calcination. The net structure of the porous nanosheets allows the MnCo2 O4 @NiO electrode to have an excellent specific surface area so as to provide more active sites in the Faraday reaction. Therefore, the MnCo2 O4 @NiO electrode has an ultrahigh specific capacitance of up to 508.3 F g −1 at a current density of 2 A g −1 and excellent cycle stability of 89.7% capacitance retention after 2000 cycles at a current density of 10 A g −1 . With their unique structure, these composite materials show great potential for use as high-performance supercapacitor anodes in practical applications.